2007
DOI: 10.1002/ange.200601737
|View full text |Cite
|
Sign up to set email alerts
|

Fortschritte bei asymmetrischen Phasentransferkatalysen

Abstract: Der Einsatz chiraler nichtracemischer Oniumsalze und Kronenether als wirksame Phasentransferkatalysatoren ist intensiv untersucht worden. Gesucht wurde dabei vorrangig nach Wegen zur enantioselektiven Knüpfung von Kohlenstoff‐Kohlenstoff‐ oder Kohlenstoff‐Heteroatom‐Bindungen unter milden Bedingungen in Zweiphasensystemen. Eine Voraussetzung für optimale asymmetrische Katalysen ist die Abstimmung des Katalysators auf die jeweilige Reaktion und, daraus resultierend, die Bildung definierter chiraler Ionenpaare, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
6

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 203 publications
(27 citation statements)
references
References 241 publications
(146 reference statements)
0
21
0
6
Order By: Relevance
“…General protocol: A flame-dried tube under argon atmosphere (1 atm) was charged with [IrA C H T U N G T R E N N U N G (ppy) 2 A C H T U N G T R E N N U N G (dtbbpy)]PF 6 catalyst (9, 1.3 mg, 1.5 mmol) in dry dichloromethane (1 mL) or dry acetonitrile (1 mL). Enecarbamate 1 (0.1 mmol), diethyl bromomalonate (2 a, 37 mL, 0.2 mmol), Et 3 N (28 mL, 0.2 mmol) and alcohol 3 (1 mmol) were added in this order.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…General protocol: A flame-dried tube under argon atmosphere (1 atm) was charged with [IrA C H T U N G T R E N N U N G (ppy) 2 A C H T U N G T R E N N U N G (dtbbpy)]PF 6 catalyst (9, 1.3 mg, 1.5 mmol) in dry dichloromethane (1 mL) or dry acetonitrile (1 mL). Enecarbamate 1 (0.1 mmol), diethyl bromomalonate (2 a, 37 mL, 0.2 mmol), Et 3 N (28 mL, 0.2 mmol) and alcohol 3 (1 mmol) were added in this order.…”
Section: Methodsmentioning
confidence: 99%
“…The a-alkylation of imines is a valuable carbon-carbon bond-forming strategy, which is still an underdeveloped area [1][2][3] despite the synthetic potential of its a-branched imine products. [4] The direct C À H bond functionalization of imines with alkyl halides has proven challenging, owing to competing side reactions, such as Mannich condensation, Nalkylation, and hydrolysis.…”
mentioning
confidence: 99%
“…Presently, nonmetal-based phase-transfer catalysts (PTCs) and organocatalysts2 have been deployed to great effect for these reactions 3. Corey et al first reported the conjugate addition of 1 to acrylates and enones with notable enantioselectivity (>90 % ee ) in the presence of an N-alkylated cinchonidine salt 4.…”
mentioning
confidence: 99%
“…Dabei wird zum einen die Anziehung zwischen der Benzyleinheit des Katalysators und dem p-System des Iminium-Intermediats im cis-TS Q genutzt. Zum anderen wird die sterische Hinderung zwischen dem Gegenion (C 6 toren. So wurde gezeigt, dass die Salze von 9-Amino-9-desoxyepichinin (XXIXa) und 9-Amino-9-desoxyepihydrochinin (XXIXb), die durch eine Mitsunobu-Reaktion an der OHGruppe der Cinchona-Alkaloide in einer einzigen Stufe leicht zugänglich sind, effektive Katalysatoren zur Enon-Aktivierung darstellen (Schema 47).…”
Section: Katalyse Mit Chiralen Primären Aminenunclassified